A recurrent de novo variant supports KCNC2 involvement in the pathogenesis of developmental and epileptic encephalopathy. Issue 11 (27th August 2021) - Rydzanicz, Małgorzata; Zwoliński, Piotr; Gasperowicz, Piotr; Pollak, Agnieszka; Kostrzewa, Grażyna; Walczak, Anna; Konarzewska, Magdalena; Płoski, Rafał
Abstract: Developmental and epileptic encephalopathies (DEE) are a heterogenous group of conditions characterized by the co‐occurrence of epilepsy and intellectual/developmental disability. Despite several known DEE‐related genes, including these encoding ion channels, still many cases remain without molecular diagnosis. Here, we present a 2‐year‐old girl with severe DEE in whom whole exome sequencing revealed de novo p.(Val471Leu) variant in the KCNC2 encoding Kv3.2, a voltage‐gated potassium channel. To the best of our knowledge, this is the third DEE case due to KCNC2 mutation. Our clinical and molecular findings, particularly the recurrence of p.(Val471Leu) in patient with similar clinical phenotype, further support KCNC2 as a novel DEE‐associated gene.